Hypertensive Disorders of Pregnancy: Common Clinical Conundrums. Issue 4 (April 2022) - Ohamadike, Onyinye; Lim, Stephanie L.; Siegel, Anne; Zemtsov, Gregory; Kuller, Jeffrey A.; Dotters-Katz, Sarah
Abstract : Importance: Hypertensive complications of pregnancy comprise 16% of maternal deaths in developed countries and 7.4% of deaths in the United States. Rates of preeclampsia increased 25% from 1987 to 2004, and rates of severe preeclampsia have increased 6.7-fold between 1980 and 2003. Objective: The aim of this study was to review current and available evidence for common clinical questions regarding the management of hypertensive disorders of pregnancy. Evidence Acquisition: Original research articles, review articles, and guidelines on hypertension in pregnancy were reviewed. Results: Severe gestational hypertension should be managed as preeclampsia with severe features. Serum uric acid levels can be useful in predicting development of superimposed preeclampsia for women with chronic hypertension. When presenting with preeclampsia with severe features before 34 weeks, expectant management should be considered only when both maternal and fetal conditions are stable. In the setting of hypertensive disorders of pregnancy, oral antihypertensive medications should be initiated when systolic blood pressure is greater than 160 mm Hg or when diastolic blood pressure is greater than 110 mm Hg, with the most ideal agents being labetalol or nifedipine. Furthermore, although risk of preeclampsia recurrence in future pregnancy is low, women with a history of preeclampsia should be managed with 81 mg aspirin daily for preeclampsia prevention. Conclusion and Relevance: Despite the frequency with which hypertensive disorders of pregnancy are encountered clinically, situations arise frequently with limited evidence to guide providers in their management. An urgent need exists to better understand this disease to optimize outcomes for impacted patients. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After completing this activity, the learner should be better able to describe the diagnosis and delineation between various preeclampsia spectrum disorders; distinguish imitators of preeclampsia from preeclampsia; and explain best practices for management of various clinical conundrums related to hypertensive disorders of pregnancy.